Antithrombin III And Plasminogen Levels In Moderate And Severe Trauma - Dombrose, F A; Seyfer, A E; Callahan, J (Thrombosis and Haemostasis, 1981)
Functional and immunologic levels of antithrombin III (ATIII) and plasminogen were assessed in three groups of nine patients each: elective surgery, moderate and severe trauma. Patients otherwise healthy were classified as follows: I, elective extremity surgery, no blood transfusions, normal coagulation screening tests (14-50y); II, isolated, moderately severe trauma (e.g., replantation or revascularization of one or more digits), no transfusions (14-56y); and III, Isolated, severe trauma to extremities, with replantation and revascularization of a severed arm or leg, receiving 1-4 units of whole CPD blood (20-59y). Preoperative, intraoperative (2 hr into surgery) and 24 hr postoperative values were measured. Group III only had intraoperative sampling, with the exception of two patients who had preoperative values prior to any transfusions. A detailed statistical comparision was made (at the 95% confidence level) of the differences in ATIII activity, ATIII antigen level, the ratio of ATIII activity-to-antigen and plasminogen activity among categories within and between groups. The data suggest that elective surgery and moderate trauma had virtually the same effect on ATIII and plasminogen. Activity and antigen values decreased intraoperatively but on the average not enough to be out of the acceptable range. During the convalescent period most ATIII values returned to their preoperative level while most plasminogen values continued to decline somewhat (although still in the acceptable range). By contrast, both ATIII and plasminogen values in the severe trauma group were markedly depressed compared to preoperative levels In either group I or II. Four of the patients in this group suffered postoperative thrombosis and loss of an extremity even though the limb was initially viable. The transient lowering of both ATIII and available plasminogen is undoubtedly most critical when surgical stress is superimposed on existing trauma.